2023
DOI: 10.3389/fnut.2022.1092846
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the gut microbiome in esports players compared with those in physical education students and professional athletes

Abstract: IntroductionEsports is a category of competitive video games that, in many aspects, may be similar to traditional sports; however, the gut microbiota composition of players has not been yet studied.Materials and methodsHere, we investigated the composition and function of the gut microbiota, as well as short chain fatty acids (SCFAs), and amino acids, in a group of 109 well-characterized Polish male esports players. The results were compared with two reference groups: 25 endurance athletes and 36 healthy stude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Barton et al (2018) extended these findings to demonstrate that the functional capacity of the athlete's microbiota was significantly enhanced, compared to controls, such that metabolic byproducts of amino acids and carbohydrates, along with SCFA concentrations were elevated ( 106 ). The few other studies in athletic populations have demonstrated varied results, with some reporting similar changes to the gut microbiome as above ( 107 , 108 ), while other report no differences ( 109 , 110 ). From athletes to normal healthy young adults, it has been reported that cardiorespiratory fitness level is highly correlated with the composition and diversity of the gut microbial community.…”
Section: Influence Of Physical Activity/exercise On the Aging Microbiomementioning
confidence: 83%
“…Barton et al (2018) extended these findings to demonstrate that the functional capacity of the athlete's microbiota was significantly enhanced, compared to controls, such that metabolic byproducts of amino acids and carbohydrates, along with SCFA concentrations were elevated ( 106 ). The few other studies in athletic populations have demonstrated varied results, with some reporting similar changes to the gut microbiome as above ( 107 , 108 ), while other report no differences ( 109 , 110 ). From athletes to normal healthy young adults, it has been reported that cardiorespiratory fitness level is highly correlated with the composition and diversity of the gut microbial community.…”
Section: Influence Of Physical Activity/exercise On the Aging Microbiomementioning
confidence: 83%
“…These two probiotic species are well represented in commercial products [ 66 ]. However, the effects of probiotic products on athletic performance are still poorly understood [ 67 ]. While we did not determine strain-level taxonomy from our samples [ 68 ], it was interesting that our results support the beneficial effects of Bifidobacterium longum and Bifidobacterium adolescentis on general fitness and cardiorespiratory fitness.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic bacterial DNA was extracted from 200 mg of feces using a QIAamp Fast DNA Stool Mini Kit (Qiagen, Hilden, Germany) according to the manufacturer’s instructions ( 26 ). DNA was quantified using fluorimetry with the Qubit dsDNA High Sensitivity Assay (Thermo Fisher Scientific, Carlsbad, CA, USA).…”
Section: Methodsmentioning
confidence: 99%